2017
DOI: 10.3389/fphys.2017.00360
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Ambiguities in the LF/HF Ratio: LF-HF Scatter Plots for the Categorization of Mental and Physical Stress from HRV

Abstract: It is generally accepted that the activities of the autonomic nervous system (ANS), which consists of the sympathetic (SNS) and parasympathetic nervous systems (PNS), are reflected in the low- (LF) and high-frequency (HF) bands in heart rate variability (HRV)—while, not without some controversy, the ratio of the powers in those frequency bands, the so called LF-HF ratio (LF/HF), has been used to quantify the degree of sympathovagal balance. Indeed, recent studies demonstrate that, in general: (i) sympathovagal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
165
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(171 citation statements)
references
References 21 publications
3
165
0
3
Order By: Relevance
“…31 In addition, heart rate and HRV analysis have been used for estimation of mental stress and athlete's fi tness levels, fatigue and overload. 5 The quantifi cation of ANS function is feasible by calculating several HRV parameters according to time-domain, frequency-domain and nonlinear analysis of consecutive RR intervals. 1 These indices represent different components of the sympathetic and/or parasympathetic system of the ANS.…”
Section: Hrv Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In addition, heart rate and HRV analysis have been used for estimation of mental stress and athlete's fi tness levels, fatigue and overload. 5 The quantifi cation of ANS function is feasible by calculating several HRV parameters according to time-domain, frequency-domain and nonlinear analysis of consecutive RR intervals. 1 These indices represent different components of the sympathetic and/or parasympathetic system of the ANS.…”
Section: Hrv Fundamentalsmentioning
confidence: 99%
“…Decreased HRV has been reported as a predictive factor for adverse outcomes in disease states and has been found to be associated with fatigue, stress, and even burnout during athletic performance. [3][4][5] High HRV is an indication of a better general health status as it allows better adjustment to external and internal stimuli. 6 Due to the fact that traditional HRV recording methods, such as using electrocardiography (ECG) and specialized software, often involve expensive equipment, which is primarily found in research laboratories, alternative methods have been used, yet, with variable results.…”
Section: Introductionmentioning
confidence: 99%
“…HRV analysis quantifies variations in heartbeat intervals, offering a non-invasive measure of autonomic function, as it reflects the actions of the sympathetic and parasympathetic nervous systems. The simplest measure of HRV is determined by the standard deviation of the difference between consecutive RR intervals (SDNN), but many other measures of HRV continue to be developed [6, 7]. Currently, HRV analyses can include not only linear measures in time and frequency domains but also several non-linear metrics derived from complexity analysis [8].…”
Section: Introductionmentioning
confidence: 99%
“…The controversy surrounding this conjecture was highlighted in several studies where the effects of mental stress on the LF and HF components of HRV were found to be neither consistent, nor correlate with the trends seen in physical stress (Berntson et al, 1994). However, despite the uncertainty over the physiological interpretatio ns of the LF and HF components, and whether or not they respectively represent the activities of the SNS and PNS (Berntson et al (1994), Eckberg (1997), Berntson and Cacioppo (2004), Billman (2013) and von Rosenberg et al (2017)), it comes as a surprise that until recently, the theories regarding the relationships between stress, HR and HRV were developed without accounting for, or appreciating sex differences. To this end, this work aims to quantify and demystify the effects of sex differences on the dynamics of ECG, in a proof-of-concept study based on ECG recordings from participants who have been subjected to a mental stressor.…”
Section: Introductionmentioning
confidence: 99%